2020
DOI: 10.5423/ppj.oa.03.2019.0072
|View full text |Cite
|
Sign up to set email alerts
|

Hexanal Vapor Induced Resistance against Major Postharvest Pathogens of Banana (Musa acuminata L.)

Abstract: Hexanal, a C-6 aldehyde has been implicated to have antimicrobial properties. Hence, this study was conducted to determine the antifungal activities of hexanal vapor against major postharvest pathogens of banana viz., Colletotrichum gloeosporioides and Lasiodiplodia theobromae. The pathogens were cultured in vitro and exposed to hexanal vapor at 600, 800, 1,000 and 1,200 ppm. Mycelial growth of both fungal pathogens were inhibited completely at 800 ppm and the incidence of anthracnose and stem-end rot diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…In addition, as explained above, inhibitory ant chemicals may be tested as agents that can be used to increase storage and shelf life of fruits and vegetables. Hexanal, which is produced by some ant species, is already in use in fruit sprays, as it inhibit post-harvest diseases and, at the same time, is harmless to humans (Anusha et al, 2016;Dhakshinamoorthy et al, 2020). Other ant compounds may have similar potentials.…”
Section: Final Notes On Future Directionsmentioning
confidence: 99%
“…In addition, as explained above, inhibitory ant chemicals may be tested as agents that can be used to increase storage and shelf life of fruits and vegetables. Hexanal, which is produced by some ant species, is already in use in fruit sprays, as it inhibit post-harvest diseases and, at the same time, is harmless to humans (Anusha et al, 2016;Dhakshinamoorthy et al, 2020). Other ant compounds may have similar potentials.…”
Section: Final Notes On Future Directionsmentioning
confidence: 99%
“…9 It has been reported that hexanal possessed broad-spectrum antimicrobial activity against fungus and bacteria. 10,11 For example, hexanal inhibited the growth of Penicillium expansum, Botrytis cinerea, Escherichia coli, Pseudomonas fluorescens, and Erwinia carotovora. 10,12,13 Due to its "green" odor, hexanal was often applied to control pathogenic and spoilage bacteria associated with fruits, vegetables, and their products.…”
Section: Introductionmentioning
confidence: 99%
“…10,12,13 Due to its "green" odor, hexanal was often applied to control pathogenic and spoilage bacteria associated with fruits, vegetables, and their products. 10,14,15 Significantly, hexanal is also one of the characteristic flavor components of aquatic products, 16,17 which is often ignored. To the best of our knowledge, there is few report on the anti-V. parahaemolyticus effect of hexanal.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations